Complaints of the arm, neck and shoulder among computer office workers in Sudan: a prevalence study with validation of an Arabic risk factors questionnaire - Hassan Amar A; Staal J Bart; Eltayeb Shahla M; Awad Salwa S; de Bie Rob A (BMC, 2008)
Abstract Background Complaints of the arm, neck and/or shoulders (CANS) in general and computer-related disorders in particular affect millions of computer office workers in Western developed countries. However, with the widespread use of computer systems in developing countries, the associated musculoskeletal complaints are yet to be investigated. Aim To study the prevalence of work-related CANS, among computer office workers in Sudan, and to test the psychometric properties of a translated Dutch questionnaire in Arabic language. Methods In 2005 282 computer office workers at a mobile telecommunication company and three banks in Khartoum, Sudan, received an Arabic language version of the validated Maastricht upper extremity questionnaire (MUEQ). The questionnaire holds 109 items covering demographic characteristics, in addition to six main domains (i.e. work station, body posture, break time, job control, job demands and social support) assessing potential physical and psychosocial risk factors. Forward/backward translation of the MUQE was done independently by two different translators. Prevalence over the past year were computed for CANS. Further, the psychometric properties of the Arabic questionnaire were investigated (i.e. factor structure and reliability) and cross-validation was carried out. Results The response rate of the questionnaire was 88% (n = 250). The one-year prevalence of CANS showed that 53% of the respondents could be classified as mild cases. The highest incidences were found for neck and shoulder symptoms (64% and 41% respectively). The analysis of the psychometric properties of the scale resulted in the identification of 2 factors for each of the 6 domains (i.e. office equipment, computer position, head and body posture, awkward body posture, autonomy, quality of break time, skill discretion, decision authority, time pressure, task complexity, social support, and work flow). The calculation of internal consistency and cross validation provided evidence of reliability and lack of redundancy of items. Conclusion The prevalence of CANS among the targeted population seems to correspond strongly with prevalence of CANS in Western developed countries. The Arabic translation of the MUEQ has satisfactory psychometric properties to be used to assess work-related risk factors for the development of CANS among computer office workers in Sudan.